Hubungan Hubungan Tingkat Pengetahuan, Sikap dan Nutrisi Ibu Nifas dengan Pecepatan Penyembuhan Luka Perineum di Puskesmas Grogol, Kotasari Tahun 2022 - Sidqi, Lisana (MPI Press, 2024)
Introduction: Improper treatment of the perineum can lead to infection in the perineum. Perineal infection can cause complications of both bladder and birth canal infections. Objectives: The purpose of this study was to determine the correlation between the level of knowledge, attitudes, and nutrition of postpartum mothers with accelerated healing of perineal wounds at the Grogol Health Center, Kotasari in 2022. Method: The research design used was cross sectional. The sampling technique in this study used total sampling technique for all 53 postpartum mothers at Puskesmas Grogol, Sukabumi Regency, using total sampling technique. The data collection instrument in this study used questionnaires and hypothesis testing with chi-square test. Result: The relationship between postpartum maternal attitudes and knowledge with the acceleration of perineal wound healing obtained maternal p-value 0.000 < α:05 so that H0 is accepted and maternal knowledge p-value 0.012 < α:05. The relationship between postpartum maternal nutrition and accelerated perineal wound healing with a p-value of 0.545 < α: 0.05. Conclusion: There is a relationship between the attitude and knowledge of postpartum mothers with the acceleration of perineal wound healing and there is no relationship between postpartum maternal nutrition and the acceleration of perineal wound healing at the Grogol Health Center.